Innovative Foldable Tire Changer: Design and Fabrication (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Changing a flat tire is a difficult and challenging task for vehicle owners, causing inconvenience, delays and benefits if mismanaged. This project addresses the need to help those who may be deficient in technical proficiency or physical strength when changing tires. This research is to design and fabricate a portable tool that facilitates the tire changing process to reduce the risk of injuries. The project methodology involves the process of developing a Foldable Tire Changer assistive device, a lightweight and ergonomic device suitable for tire sizes with a radius of 14-20 inches. The main features are its foldable nature for easy storage, minimal physical effort required and a fast and safe tire changing process. A stress analysis was conducted to assess the performance of the tool under the loads associated with tire weight. The Finite Element Analysis illustrates that the product design for tire size 175/65 R14 (small car), 185/55 R15 (sedan & MPV’s car) and T115/70/D14 (SUV’s car) with 6.5, 9.1 and 15 kg respectively shows the stress analysis result indicating that the design is predominantly stable and possesses the capability to endure the applied forces. Meanwhile, experiments demonstrate that with comparison of tire changing processes, the time taken is less in between 65-70% rather than traditional method. Therefore, in align with the United Nations Sustainable Development Goal (SDG) 9, this tool fosters innovation in accessible infrastructure as a versatile automotive accessory. This assistive device provides a pragmatic solution aimed at mitigating injuries and augmenting efficiency in tire-replacement activities.